Clear Disclosure of Hierarchical Chirality Transfer Mechanism and Wide Full‐Color and White‐Light CPL Emissions with Both High glum and Intensity by TPE Helicates - Ye, Feng‐Ying; Hu, Ming; Du, Cong; Yu, Wei; Zhou, Xing‐Ping; Liu, Minghua; Zheng, Yan‐Song (Advanced optical materials, 2023)
Chirality transfer and amplification play key role on research of chiral materials, but it is still a challenge to clearly disclose the chirality transfer mechanism. Here, tetraphenylethylene helicate (TPEH) with aggregation‐induced emission enhancement effect is doped into achiral nematic liquid crystal (NLC) to furnish a system of excellent chirality transfer and amplification for the first time. It is found that left‐handed helical (M) TPEH molecule with four phenyl rings sloping right‐down makes a staggered overlap with other M‐TPEH at right‐up direction for attenuating the repulsive force between phenyl rings, which is further overlapped into a right‐handed helix (P) and then drives NLC array layers to the P‐LC phase. Consequently, M‐TPEH molecule leads to P‐LC phase, while P‐TPEH arouses M‐LC phase. Remarkably, this chirality transfer can amplify the circularly polarized luminescence (CPL) of TPEH by 100‐fold and give a large absolute CPL dissymmetric factor (glum) of 0.21. Moreover, the chirality can be even transferred to other achiral fluorescence dyes, and both high absolute glum of up to 0.37 and high fluorescence quantum yield (Φf) of 92% are obtained. Consequently, a customized wide full‐color and white‐light CPL emission from violet to near infrared which is closer to natural light is obtained. Fluorophores with helical chirality are utilized to induce and boost chirality in liquid crystal for the first time and the hierarchical chirality transfer, inversion, and amplification mechanism are clearly revealed unprecedentedly. Exceptionally, full‐color and white‐light circularly polarized luminescence with inverse directions in one emission spectrum and both high glum and high quantum yield are obtained by tetraphenylethylene helicates.